Formation of fan psychological ownership and Its influence on fan enthusiasm: a hybrid approach using PLS-SEM and fsQCA - Huang, Qiuhao; Zou, Yanxue (Frontiers in Psychology, 2025)
Driven by digital platforms and algorithmic ecosystems, contemporary fan culture has evolved into an unprecedented form of intensity and density. Fans willingly devote vast amounts of data labor, daily engagement in comment management, and financial voting to support their idols. Although prior research has primarily explained fan behavior through parasocial relationships or identity-based mechanisms, these approaches fall short of accounting for fans’ sovereignty-like sense of responsibility and sustained commitment. To address this gap, the present study introduces psychological ownership as a core explanatory lens and proposes a dual-pathway model consisting of idol–fan psychological ownership and fans’ collective psychological ownership to uncover the psychological drivers of fan enthusiasm in the digital era. Using a mixed-method design integrating Partial Least Squares Structural Equation Modeling (PLS-SEM) and fuzzy-set Qualitative Comparative Analysis (fsQCA), we analyzed survey data from 402 Chinese fans of fostered idols (Teens in Times and TFBOYS). PLS-SEM results indicate that self-investment, intimate interaction, and cultural symbol value positively contribute to the formation of both idol-fan psychological ownership and fans’ collective psychological ownership. In contrast, perceived control and fan emotionality predict only idol–fan psychological ownership, exerting no significant effect on collective ownership. Both forms of psychological ownership significantly enhance fan enthusiasm. Complementing these findings, fsQCA identified three distinct configurations—interaction-oriented, control-oriented, and emotion-driven patterns—that lead to high fan enthusiasm, revealing the causal complexity underlying fan behavior. This study extends psychological ownership theory into the domain of digital fan culture and enriches theoretical understandings at the intersection of fan studies and consumer behavior. The findings also offer important practical insights for idol-industry managers, brand strategists, and platform governance practitioners.